Influence of Mg/CTAB ratio on the structural, physicochemical properties and catalytic activity of amorphous mesoporous magnesium silicate catalysts. Issue 66 (26th November 2019) - Tan, Kok-Hou; Iqbal, Anwar; Adam, Farook; Abu Bakar, N. H. H.; Ahmad, M. N.; Yusop, Rahimi M.; Pauzi, Hariy
Abstract : Increasing the magnesium content in direct synthesis will lead to the formation of different magnesium active sites that increase the styrene oxide selectivity under the same reaction conditions. Abstract : This study investigated the physicochemical and catalytic properties of mesoporous magnesium silicate catalysts prepared at various Mg/CTAB ratios (0.25, 0.50, 0.75 and 1.00). The XPS analysis detected a mixture of enstatite and magnesium carbonate species when the Mg/CTAB ratio was 0.25, and 0.50. A mixture of forsterite and magnesium carbonate species were detected when the Mg/CTAB ratio was 0.75 whereas for the Mg/CTAB ratio of 1.00, enstatite and magnesium metasilicate species were detected. A catalyst with the Mg/CTAB ratio of 1.00 demonstrated the highest catalytic activity in the oxidation of styrene. The styrene conversion rate was 59.0%, with 69.2% styrene oxide (StO) selectivity. The H2 O2 molecules were activated regio-specifically by the magnesium species to prevent rapid self-decomposition while promoting selective interaction with styrene. All the parameters that influence the styrene conversion and product selectivity were evaluated using analysis of variance (ANOVA) with Tukey's test. The ANOVA analysis showed that the reaction time (h), Mg/CTAB ratio, styrene/H2 O2 ratio, catalyst loading (mg) and temperature (°C) affect styrene conversion and product selectivity (StO) significantly ( p < 0.05). The oxidation of styrene was well fitted to the pseudo-first-order model. The activation energy, E a of the catalysed styrene epoxidation reaction was calculated to be 27.7 kJmol −1 . The catalyst can be reused several times without any significant loss in its activity and selectivity. The results from this study will be useful in designing and developing low cost, high activity catalysts from alkaline earth metals.